Utilisation of recycled concrete as replacing of coarse aggregate for the concrete manufacturing - Aguilar, Carlos; Muñoz, María Pía; Loyola, Oscar (Revista Ingeniería de Construcción, 2005)
The present research analyzed the properties of concretes made with Portland Pozzolan cement and recycled aggregate obtained of demolished concretes to be propused as an alternative to a potential lack of aggregate natural in urban areas. An experimental program was carried out to study the effect of the amount and type of cement and recycled aggregate type on the concrete properties. The results showed decreases in all the physical properties of recycled aggregates. Considering fresh concrete, the concretes made with recycled aggregates presented slightly lower values with respect to the natural aggregate concretes. Similarly in hardened concrete, concrete made with recycled aggregate presented diminished values of strength and modulus of elasticity. It highlights that the total substitution of natural aggregate by recycled concrete, implies smaller losses to those presented in concretes with partial substitution of aggregate. It is estimated that the mortar adhered to the surface of the aggregate of recycled concrete is the critical factor that affects the properties of the recycled aggregate concrete.